Antebrachiocarpal luxation in a cat - Voss, K.; Geyer, H.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A complete palmar antebrachiocarpal luxation due to rupture of the medial collateral ligament was diagnosed in a cat. Complete antebrachiocarpal luxation in dogs is generally associated with the disruption of multiple carpal ligaments. A comparative anatomical study of cadavers of five cats and five dogs revealed that, unlike in dogs, the medial collateral ligament in cats consists of only one branch, which extends from its dorsoproximal attachment on the radius obliquely to its palmarodistal attachment on the radial carpal bone. The oblique course of the ligament likely opposes palmar dislocation of the radial carpal bone rather than medial opening of the radiocarpal joint.In this present reported case, adequate joint stability was achieved by replacing the medial collateral ligament using two 1.5-mm cortical screws and a3.5 (metric gauge) polypropylene figure-8 suture sling. Minimal signs of osteoarthrosis developed three months after surgery, but functional outcome at six months was very satisfactory.
Keywords: Cat; carpus; medial collateral ligament; antebrachiocarpal luxation